Strengthening the Enforcement of Geneva Convention Policies in Response to Israeli Violations - Mahmoud W M Abu Wazna; Mahmoud Elsayed Atyea Abdasmad; Muhammad Mas'udi; Carrel Ticualu (Contrarius Indonesia, 2026)
International humanitarian law regulates armed conflict through a framework of customary and treaty-based norms, with the Geneva Conventions imposing legally binding duties on conflict parties to safeguard civilians and civilian objects. Despite this normative framework, enforcement mechanisms continue to demonstrate limited effectiveness, particularly in protracted armed conflicts. This study examines alleged violations of the Fourth Geneva Convention during the 2023, armed conflict in the Gaza Strip and evaluates the capacity of existing international humanitarian law enforcement mechanisms to protect Palestinian civilians. The research further analyzes avenues for strengthening judicial accountability through international criminal justice processes. Employing a socio-legal research design, the study integrates just war theory and law enforcement theory and applies qualitative descriptive-analytical methods to primary and secondary legal materials. The findings demonstrate that, first parties to the conflict committed serious breaches of the Fourth Geneva Convention affecting civilian protection. Second, international enforcement mechanisms, including international judicial institutions, operated ineffectively due to political interference and limited State compliance. Third, expansive interpretations of military necessity weakened accountability for grave breaches of international humanitarian law. The study concludes that strengthening enforcement requires restricting such interpretations and ensuring the consistent implementation of international criminal court decisions to enhance legal accountability.